A review on application and optimization processes used for wear testing machine (pin on disc apparatus). (2022) - Kaushik, Jalaj; Ahmad Khan, Haseeb; Tiwari, Abhinav; Nafees, Khalid; Varshney, Sanjeev; Singh, S.P.
Abstract: This paper explored the techniques that may be employed to perform a wear test utilising a pin on disc apparatus, of the wear testing machine. The apparatus comprises of a horizontal spinning disc with a calibrated dead weight pin kept on it. The goal of this work is to evaluate the investigations conducted by researchers on various materials. As wear is a leading cause of mechanical failure, the author(s) computed wear characteristics and then performed investigations on different pin on disc equipment. Wear optimization has been done by using analytical tools such as ANSYS and ABAQUS. This investigation yields favourable findings in terms of machine operation and durability.